THE INTENSITY OF PLAYING ONLINE GAMES ON THE VIOLENCE AND AGGRESSIVE BEHAVIOR STUDENTS - Maria Terok; Tinekke Tololiu; Nanda Rompis (POLTEKKES KEMENKES MANADO, 2018)
Background: Game online is played by more than one player (multiplayer) simultaneously, anywhere and anytime using a laptop, computer or smartphone that is supported by an internet connection. Too often playing online games has an effect on personality because it tends to absorb and mimic everything that is seen so that it triggers aggressive behavior that can unwittingly kill the character of others, because swearing, harsh words, insults, and ridicule makes someone very hurt and the consequences will painful and settled in someone's memory. Aims: of this research study is to find out whether there is a relationship between the intensity of playing violent online games and the aggressive behavior of students. Methods and Result: The study design used correlation analytic with a cross-sectional approach on 32 respondents who were determined by purposive sampling. Data collection questionnaire aggressive behavior and intensity of playing online games. The test used Chi-square (x2) statistics. The results showed the intensity of playing online games with the most violence at a moderate level, namely 18 students (56.3%), with moderate aggressive behavior of 20 students (62.5%). Conclusion of the research conducted at class X students of SMK Negeri 1 Tumpaan is that there is a very significant relationship on the intensity of playing violent online games with aggressive behavior of students with the statistical test results p-value = 0.002 which is smaller than α = 0.05. Suggestions that students use free time by doing more useful things to avoid aggressive behavior and health problems caused by playing violent online games with a long time intensity.